Is Dating Behavior in Digital Contexts Driven by Evolutionary Programs? A Selective Review - Ponseti, Jorge; Diehl, Katharina; Stirn, Aglaja Valentina (Frontiers in Psychology, 2022)
In recent years, millions of citizens all over the world have used digital dating services. It remains unknown to what extent human sexuality will be changed by this. Based on an evolutionary psychological perspective, we assume that sexual selection shaped behavioural tendencies in men and women that are designed to increase the reproductive fitness. These tendencies are referred to as sexual strategies. Males and females sexual strategies differ according to sex-dimorphic reproductive investments. We assume that this inheritance will affect human sexuality also in a digital future. To evaluate this assumption, we conducted a selective review of studies on digital dating services. Based on sexual selection theory, we derived a number of hypotheses regarding how men and women will use digital dating services typically and how the use of digital dating services might affect sexual wellbeing. Out of an initial data set of 2,568 records, we finally reviewed a set of 13 studies. These studies provided support for the notion that men and women act in the digital dating area according to sex-typical strategies. However, sometimes the circumstances of digital dating affect communication flow, e.g., in that men are even more active in establishing contacts than they are in real world conditions. Overall, women appear to accomplish their sexual goals in digital dating arenas more than men do given a surplus of male demand. Our results suggest that future human sexuality will be impacted by an interaction of both: sex-dimorphic ancient sexual strategies and new technologies.